Analysis of the Effectiveness of IC Tester Demonstrator Tools in Accelerating the Diagnosis of TTL Logic Gate Damage: A Quasi-Experimental Study at UMK - Setyaningsih, Noor Yulita Dwi; Wibowo, Budi Cahyo; Rozaq, Imam Abdul (LPPM Universitas Dian Nuswantoro, 2025)
In the practicum process for testing the condition of the TTL IC, it is still done manually and requires time to complete. With class conditions where students who participate have different levels of understanding. The smooth implementation of digital electronics practicum activities will be hampered if the ICTTL (Integrated Circuit Transistor Transistor Logic) components used in the experiment do not have normal operating functions. This study analyzes the effectiveness of the IC tester teaching aid in accelerating the diagnosis of TTL logic gate damage through a quasi-experimental study at UMK. Data were taken from 9 students grouped by ability ( Good , Sufficient , Less ) by comparing the time of manual testing and testing using the teaching aid . From the results, it was found that the teaching aid provided good effectiveness in the TTL IC testing process, namely 60-72% by reducing the average from 121-159 seconds (manual testing) to 45-58 seconds/student. The consistency of the time required to check the IC for all groups of student abilities became the same after using this teaching aid Keywords - Demonstration Tools, IC Tester, Effectiveness, Quasi-Experiment